Corrosion-resistant iron-based alloy powder and preparation method thereof

By preparing a specific formula of corrosion-resistant iron-based alloy powder, the problem of ferro-based alloy materials being easily corroded in acidic or alkaline environments is solved, and the corrosion rate and excellent mechanical properties are significantly reduced in acidic, alkaline and salt solutions are achieved.

CN119685723AActive Publication Date: 2025-03-25JIANGSU VILORY ADVANCED MATERIALS TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510205751.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-25
Estimated Expiration
2045-02-25

AI Technical Summary

Technical Problem

Ferro-based alloy materials are susceptible to corrosion in acidic or alkaline environments, and the prior art is difficult to solve this problem essentially.

Method used

A corrosion-resistant iron-based alloy powder is used, and its formulation includes chromium 5.3-7.5%, nickel 1.0-2.0%, molybdenum 4.5-7.0%, titanium 2.0-4.5%, carbon 1.4-1.8%, rare earth elements 0.5-1.5%, impurities 0.05-0.13% and balance iron. It is heated by a vacuum induction furnace and treated with atomization nozzle under nitrogen and water.

Benefits of technology

The corrosion rate of the iron-based alloy powder in acidic, alkaline and salt solutions is significantly reduced, and a dense chromium oxide protective film is formed on the surface, which improves the corrosion resistance of the iron-based alloy while maintaining excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of hard alloy, and particularly relates to corrosion-resistant iron-based alloy powder and a preparation method thereof. The corrosion-resistant iron-based alloy powder provided by the invention is prepared from 5.3%-7.5% of chromium, 1.0%-2.0% of nickel, 4.5%-7.0% of molybdenum, 2.0%-4.5% of titanium, 1.4%-1.8% of carbon, 0.5%-1.5% of rare earth elements, 0.05%-0.13% of impurities and the balance of iron. The corrosion-resistant iron-based alloy powder provided by the invention has an oxidation film on the surface, all elements in the alloy are in a passivated state, meanwhile, alloy grains are fine, grain boundary arrangement is neat, and the problem that an iron-based alloy material is easy to corrode can be essentially improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cemented carbide, and in particular relates to a corrosion-resistant iron-based alloy powder and a preparation method thereof. Background Art

[0002] Ferroalloys are alloys of one or more metal or non-metal elements fused together. They usually have excellent mechanical properties and heat resistance, so they are widely used in industrial production. Ferroalloys are widely used in the steel industry to make various types of steel. At the same time, ferroalloys are also used in electronics, aerospace, automobiles, construction and other industries to make electronic components, engine parts, building structures, etc. With the continuous advancement of science and technology and the development of industry, ferroalloys will continue to grow and develop in the future.

[0003] Metal corrosion has long been the focus of people's attention. Iron-based alloys will be corroded more or less in acidic or alkaline environments. This is because iron-based alloys generally have many small pores. In acidic or alkaline environments, the inner walls of the pores are in contact with acidic or alkaline gases or solutions for a long time, resulting in corrosion around the pores, which seriously affects the durability of iron-based alloys. The common method to improve the corrosion resistance of iron-based alloys is to form an oxide film on the surface of the iron-based alloy or to apply an anti-corrosion coating on the surface of the iron-based alloy. However, this can only delay the corrosion of the iron-based alloy material, and cannot fundamentally solve the corrosion-prone nature of the iron-based alloy material.

[0004] The Chinese patent application document with publication number CN105648340A discloses a high-density corrosion-resistant nickel-iron alloy, whose formula is: carbon 0.11-0.17%, chromium 0.36-0.42%, silicon 0.12-0.21%, titanium 0.28-0.3%, niobium 0.10-0.15%, manganese 0.25-0.32%, copper 0.10-0.30%, nickel 0.68-0.75%, sulfur 0.03-0.05%, phosphorus 0.01-0.03%, rare earth elements 0.05-0.15%, unavoidable impurities less than 0.1% and the balance iron. This formula improves the compactness and surface corrosion resistance of the die-casting alloy by controlling the content of the alloy components, but it cannot fundamentally solve the corrosion-prone characteristics of the iron-based alloy material. Summary of the invention

[0005] In order to solve the technical problems existing in the related art that the iron-based alloy materials are susceptible to corrosion and cannot be fundamentally improved, the purpose of the present invention is to provide a corrosion-resistant iron-based alloy powder and a preparation method thereof.

[0006] In order to achieve the above-mentioned invention object, the technical solution of the present invention is as follows: A corrosion-resistant iron-based alloy powder comprises the following components and their weight percentages: Chromium 5.3-7.5%, nickel 1.0-2.0%, molybdenum 4.5-7.0%, titanium 2.0-4.5%, carbon 1.4-1.8%, rare earth elements 0.5-1.5%, impurities 0.05-0.13%, and the balance iron.

[0007] Furthermore, the corrosion-resistant iron-based alloy powder includes the following components and their weight percentages: 6.6% chromium, 1.5% nickel, 6.3% molybdenum, 3.2% titanium, 1.6% carbon, 0.9% rare earth elements, 0.09% impurities, and the balance iron.

[0008] The corrosion resistance of the alloy depends on the protective properties of the surface film. The chromium in the iron-based alloy powder formula provided by the present invention can form a dense chromium oxide protective film on the alloy surface, which has the effect of blocking the corrosive medium and improving the corrosion resistance of the iron-based alloy. However, an overly thick oxide film has a large internal stress, which can easily lead to cracking of the film and thus reduce the corrosion resistance of the alloy. Therefore, the addition of chromium is particularly important. When the addition of chromium is greater than 7.5%, the iron-based alloy material reaches the level of stainless steel, but at this time the internal stress of the chromium oxide film is large, and the oxide film is easy to crack, resulting in a decrease in the corrosion resistance of the iron-based alloy material.

[0009] Molybdenum can improve the corrosion resistance of iron-based alloy materials in acidic environments, and improve the pitting corrosion and crevice corrosion resistance of iron-based alloy materials. However, the addition of molybdenum will increase the high-temperature deformation resistance of iron-based alloy materials. Therefore, the higher the content of molybdenum, the worse the high-temperature corrosion resistance of the iron-based alloy materials. During the research process, the inventors found that the addition of titanium can make the thermodynamically unstable metals in the iron-based alloy materials change from an activated state to a passivated state, thereby improving the high-temperature corrosion resistance of the iron-based alloy materials.

[0010] In conventional iron-based alloy materials, carbon is the key to the corrosion resistance of iron-based alloy materials, and the corrosion resistance of iron-based alloy materials decreases with the increase of carbon content. When the carbon content in the iron-based alloy material is lower than 1.2%, the iron-based alloy material can reach the corrosion resistance of stainless steel, but the carbon element is evenly dispersed in the iron alloy, and can play the role of a reducing agent in the preparation process of the iron-based alloy, and can reduce the oxidized metal elements in the iron-based alloy material to ensure the mechanical properties of the iron-based alloy material. The inventor has proved through a large number of experimental studies that when the carbon content is 1.4-1.8%, the corrosion resistance and mechanical properties of the iron-based alloy material are excellent.

[0011] Furthermore, the rare earth elements in the corrosion-resistant iron-based alloy powder are composed of cerium, samarium and erbium in a mass ratio of 3-7:5-9:11-13.

[0012] The inventor found in the research process that the corrosion resistance of iron-based alloys is closely related to their microstructure, mainly including two aspects: crystal defects and grain boundaries. Crystal defects such as voids, point defects, surface defects, inclusions, etc. will affect the corrosion behavior of the material. The grain boundary is an essential mechanism for corrosion resistance in the material. The grain boundary can cause voids, local oxidation and other phenomena, thereby limiting the penetration and erosion of the corrosive medium. The present invention introduces rare earth elements into the iron-based alloy powder, which can promote grain refinement and increase the grain boundaries in the iron-based alloy powder, thereby improving the corrosion resistance of the iron-based alloy powder. The inventor found that when the rare earth elements are composed of cerium, samarium, and erbium in a mass ratio of 3-7:5-9:11-13, the corrosion resistance of the iron-based alloy material is the best.

[0013] Furthermore, the rare earth elements in the corrosion-resistant iron-based alloy powder are composed of cerium, samarium and erbium in a mass ratio of 3:5:11.

[0014] Furthermore, the rare earth elements in the corrosion-resistant iron-based alloy powder are composed of cerium, samarium and erbium in a mass ratio of 5:7:12.

[0015] Furthermore, the impurities in the corrosion-resistant iron-based alloy powder are composed of antimony, arsenic, and tin in a mass ratio of 2-5:1-3:5-9. The inventors found during the research that after adding antimony, arsenic, and tin to the iron-based alloy powder, the corrosion rate of the iron-based alloy powder under acidic conditions was significantly reduced. It is speculated that these three elements reduce the active dissolution rate of the alloy under acidic conditions.

[0016] Furthermore, the impurities in the corrosion-resistant iron-based alloy powder are composed of antimony, arsenic and tin in a mass ratio of 4:2:7.

[0017] The present invention also provides a method for preparing the corrosion-resistant iron-based alloy powder, which specifically comprises: placing a formulated amount of chromium, nickel, molybdenum, titanium, carbon, rare earth elements, impurities and iron into a vacuum induction furnace and heating them until they are all melted into a liquid state, and then atomizing and drying them through an atomizing nozzle under the conditions of nitrogen as an atomizing medium and water as a cooling medium around the furnace body to obtain the corrosion-resistant iron-based alloy powder.

[0018] Compared with the prior art, the corrosion-resistant iron-based alloy powder and the preparation method thereof provided by the present invention have the following technical advantages: (1) The corrosion rate of the corrosion-resistant iron-based alloy powder provided by the present invention when immersed in an acidic solution for 72 hours at room temperature is 0.32-0.41 mm / a, the corrosion rate when immersed in an alkaline solution for 72 hours is 0.20-0.26 mm / a; the corrosion rate when immersed in a salt solution for 72 hours is 0.12-0.20 mm / a; (2) The corrosion rate of the corrosion-resistant iron-based alloy powder provided by the present invention when immersed in an acidic solution for 72 hours at 50°C is 0.50-0.58 mm / a, the corrosion rate when immersed in an alkaline solution for 72 hours is 0.35-0.43 mm / a, and the corrosion rate when immersed in a salt solution for 72 hours is 0.22-0.31 mm / a; (3) The corrosion-resistant iron-based alloy powder provided by the present invention not only has an oxide film on the surface, but also has various elements in the alloy in a passivated state. At the same time, the alloy grains are fine and the grain boundaries are neatly arranged, which can fundamentally improve the problem of easy corrosion of iron-based alloy materials. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention.

[0020] Example 1: A corrosion-resistant iron-based alloy powder and a method for preparing the same The corrosion-resistant iron-based alloy powder comprises the following components and their weight percentages: Chromium 5.3%, nickel 2.0%, molybdenum 4.5%, titanium 4.5%, carbon 1.4%, rare earth elements 1.5%, impurities 0.05%, and the balance iron.

[0021] The rare earth elements in the corrosion-resistant iron-based alloy powder are composed of cerium, samarium and erbium in a mass ratio of 3:5:11. The impurities in the corrosion-resistant iron-based alloy powder are composed of antimony, arsenic and tin in a mass ratio of 5:3:9.

[0022] The preparation method of the corrosion-resistant iron-based alloy powder is specifically as follows: after placing the formulated amount of chromium, nickel, molybdenum, titanium, carbon, rare earth elements, impurities and iron into a vacuum induction furnace and heating them until they are all melted into liquid, atomizing and drying are performed through an atomizing nozzle under the conditions of nitrogen as an atomizing medium and water as a cooling medium for the outer periphery of the furnace body to obtain the corrosion-resistant iron-based alloy powder.

[0023] Example 2: A corrosion-resistant iron-based alloy powder and a preparation method thereof The corrosion-resistant iron-based alloy powder comprises the following components and their weight percentages: Chromium 7.5%, nickel 1.0%, molybdenum 7.0%, titanium 2.0%, carbon 1.8%, rare earth elements 0.5%, impurities 0.13%, and the balance iron.

[0024] The rare earth elements in the corrosion-resistant iron-based alloy powder are composed of cerium, samarium and erbium in a mass ratio of 7:9:13. The impurities in the corrosion-resistant iron-based alloy powder are composed of antimony, arsenic and tin in a mass ratio of 2:1:5.

[0025] The preparation method of the corrosion-resistant iron-based alloy powder is specifically as follows: after placing the formulated amount of chromium, nickel, molybdenum, titanium, carbon, rare earth elements, impurities and iron into a vacuum induction furnace and heating them until they are all melted into liquid, atomizing and drying are performed through an atomizing nozzle under the conditions of nitrogen as an atomizing medium and water as a cooling medium for the outer periphery of the furnace body to obtain the corrosion-resistant iron-based alloy powder.

[0026] Example 3: A corrosion-resistant iron-based alloy powder and a method for preparing the same The corrosion-resistant iron-based alloy powder comprises the following components and their weight percentages: The corrosion-resistant iron-based alloy powder includes the following components and their weight percentages: 6.6% chromium, 1.5% nickel, 6.3% molybdenum, 3.2% titanium, 1.6% carbon, 0.9% rare earth elements, 0.09% impurities, and the balance iron.

[0027] The rare earth elements in the corrosion-resistant iron-based alloy powder are composed of cerium, samarium and erbium in a mass ratio of 5:7:12. The impurities in the corrosion-resistant iron-based alloy powder are composed of antimony, arsenic and tin in a mass ratio of 4:2:7.

[0028] The preparation method of the corrosion-resistant iron-based alloy powder is specifically as follows: after placing the formulated amount of chromium, nickel, molybdenum, titanium, carbon, rare earth elements, impurities and iron into a vacuum induction furnace and heating them until they are all melted into liquid, atomizing and drying are performed through an atomizing nozzle under the conditions of nitrogen as an atomizing medium and water as a cooling medium for the outer periphery of the furnace body to obtain the corrosion-resistant iron-based alloy powder.

[0029] Example 4: A corrosion-resistant iron-based alloy powder and a method for preparing the same The corrosion-resistant iron-based alloy powder comprises the following components and their weight percentages: Chromium 6.1%, nickel 1.6%, molybdenum 5.2%, titanium 3.1%, carbon 1.5%, rare earth elements 0.9%, impurities 0.09%, and the balance iron.

[0030] The rare earth elements in the corrosion-resistant iron-based alloy powder are composed of cerium, samarium and erbium in a mass ratio of 4:6:11. The impurities in the corrosion-resistant iron-based alloy powder are composed of antimony, arsenic and tin in a mass ratio of 3:2:8.

[0031] The preparation method of the corrosion-resistant iron-based alloy powder is the same as that of Example 3.

[0032] Comparative Example 1 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that the amount of chromium added in the formula of the iron-based alloy powder in this comparative example is 12%.

[0033] Comparative Example 2 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of scandium is used instead of titanium in the formula of the iron-based alloy powder in this comparative example.

[0034] Comparative Example 3 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of iron is used to replace titanium in the formula of the iron-based alloy powder in this comparative example.

[0035] Comparative Example 4 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 4. The difference between this comparative example and Example 4 is that the amount of carbon in the formula of the iron-based alloy powder in this comparative example is 0.5%.

[0036] Comparative Example 5 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 4. The difference between this comparative example and Example 4 is that the amount of carbon in the formula of the iron-based alloy powder in this comparative example is 2.5%.

[0037] Comparative Example 6 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of neodymium is used to replace cerium in the rare earth elements in this comparative example.

[0038] Comparative Example 7 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of praseodymium is used to replace samarium in the rare earth element in this comparative example.

[0039] Comparative Example 8 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that the rare earth elements in this comparative example are composed of cerium, samarium, and erbium in a mass ratio of 14:9:2.

[0040] Comparative Example 9 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that the impurities in the formula of the iron-based alloy powder in this comparative example are composed of antimony, arsenic, and tin in a mass ratio of 7:9:1.

[0041] Comparative Example 10 In this comparative example, the formula and preparation method of the iron-based alloy powder are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of arsenic is used to replace antimony in the impurities in this comparative example.

[0042] Test Example 1: Mechanical Properties Test Test samples: The iron-based alloy powders obtained in Examples 1 to 5, Comparative Examples 4 and 5 were statically pressed and then placed in an ultra-high temperature graphitization furnace for sintering and cooling to obtain sintered blocks; The static pressing pressure is 500MPa, and the holding time is 100s; the specific sintering process is: after placing the green body into the ultra-high temperature graphitization furnace, heating it to 200°C, sintering it at a heat preservation temperature for 1h, continuing to heat it to 600°C, sintering it at a heat preservation temperature for 2h, continuing to heat it to 1500°C, sintering it at a heat preservation temperature for 4h, continuing to heat it to 2500°C, sintering it at a heat preservation temperature for 5h, continuing to heat it to 2900°C, and sintering it at a heat preservation temperature for 5h.

[0043] Test method: Refer to GB / T 222-2002 Room temperature tensile test method for metal materials to test the yield strength and tensile strength of the test samples.

[0044] Test results: See Table 1.

[0045] Table 1 Mechanical properties test results

[0046] As can be seen from Table 1, the sintered block of the corrosion-resistant iron-based alloy provided by the present invention has excellent mechanical properties, with a tensile strength of 421.7-480.1 MPa and a yield strength of 320.4-364.6 MPa. Comparative Examples 4 and 5 are similar to Example 4. In Comparative Example 4, the amount of carbon added in the formula is reduced, but the mechanical properties of the obtained corrosion-resistant iron-based alloy sintered block are greatly reduced, which shows that in the formula of the present invention, carbon can act as a reducing agent, which can reduce the oxidized metal and ensure the mechanical properties of the material.

[0047] Test Example 2: Corrosion Resistance Test Test samples: iron-based alloy powders prepared in Examples 1 to 5 and Comparative Examples 1 to 12; Test method: Refer to JB / T 7901-2001 "Metallic Materials Laboratory Uniform Corrosion Full Immersion Test Method" to test the corrosion resistance of the test samples and calculate the corrosion rate. The test solutions used are 0.15% NaCl solution, HCl solution with a pH value of 4.5, and NaOH solution with a pH value of 8.5. The test time is 72h, and the test temperatures are 25℃ and 50℃ respectively.

[0048] Test results: The test results are shown in Table 2.

[0049] Table 2 Corrosion resistance test results

[0050]

[0051] As shown in Table 2, the corrosion rate of the iron-based alloy powder provided by the present invention in a 0.15% NaCl solution at 25°C is 0.12-0.20 mm / a, the corrosion rate in a HCl solution with a pH value of 4.5 is 0.32-0.41 mm / a, and the corrosion rate in a NaOH solution with a pH value of 8.5 is 0.20-0.26 mm / a; the corrosion rate in a 0.15% NaCl solution at 50°C is 0.22-0.31 mm / a, the corrosion rate in a HCl solution with a pH value of 4.5 is 0.50-0.58 mm / a, and the corrosion rate in a NaOH solution with a pH value of 8.5 is 0.35-0.43 mm / a. Therefore, the iron-based alloy powder provided by the present invention has good corrosion resistance.

[0052] Compared with Example 3, the amount of chromium added in Comparative Example 1 is increased, but the corrosion rate of the obtained iron-based alloy powder in acid, alkali and salt is increased, which indicates that the amount of chromium added is too large, the internal stress of the formed oxide film is increased, resulting in cracking of the oxide film and decreased corrosion resistance; other alloying elements are used to replace titanium in Comparative Examples 2 and 3, but the high-temperature corrosion rate of the obtained iron-based alloy powder is significantly increased, which indicates that the addition of titanium in the formula of the present invention can improve the high-temperature corrosion resistance of the iron-based alloy powder; Comparative Examples 6-8 change the composition and dosage ratio of rare earth elements, but the obtained iron-based alloy The corrosion rate of gold powder in acid, alkali and salt increases to varying degrees, which shows that the rare earth elements used in the present invention can refine the grains and maximize the corrosion resistance of the grain boundaries. Changing the rare earth element components or changing the dosage ratio of the rare earth elements cannot achieve the technical effect of the present invention; Comparative Examples 9 and 10 change the components and dosage of impurities in the iron-based alloy powder, but the corrosion rate of the obtained iron-based alloy powder in acid is significantly increased, which shows that the impurity components in the formula of the present invention interact with each other, play a role of 1+1>2, and can significantly improve the corrosion resistance of the iron-based alloy powder under acidic conditions.

[0053] Compared with Example 4, the amount of carbon added in Comparative Example 4 was reduced, and the corrosion rate of the obtained iron-based alloy powder in acid, alkali and salt was reduced to varying degrees. The amount of carbon added in Comparative Example 5 was increased, and the corrosion rate of the obtained iron-based alloy powder in acid, alkali and salt was significantly reduced, which shows that the amount of carbon added in the formula of the present invention has been optimized.

[0054] The above embodiments are merely illustrative of the preparation method of the present invention, and are not intended to limit the present invention. Any person skilled in the art may not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person of ordinary skill in the art without departing from the technical concept provided by the present invention are still covered by the claims of the present invention.

Claims

1. A corrosion-resistant iron-based alloy powder, characterized in that: It includes the following components and their weight percentages: Chromium 5.3-7.5%, nickel 1.0-2.0%, molybdenum 4.5-7.0%, titanium 2.0-4.5%, carbon 1.4-1.8%, rare earth elements 0.5-1.5%, impurities 0.05-0.13%, and the balance iron.

2. The corrosion-resistant iron-based alloy powder according to claim 1, characterized in that: It includes the following components and their weight percentages: 6.6% chromium, 1.5% nickel, 6.3% molybdenum, 3.2% titanium, 1.6% carbon, 0.9% rare earth elements, 0.09% impurities, and the balance iron.

3. The corrosion-resistant iron-based alloy powder according to claim 1, characterized in that: The rare earth elements are composed of cerium, samarium and erbium in a mass ratio of 3-7:5-9:11-13.

4. The corrosion-resistant iron-based alloy powder according to claim 3, characterized in that: The rare earth elements are composed of cerium, samarium and erbium in a mass ratio of 5:7:

12.

5. The corrosion-resistant iron-based alloy powder according to claim 3, characterized in that: The rare earth elements are composed of cerium, samarium and erbium in a mass ratio of 3:5:

11.

6. The corrosion-resistant iron-based alloy powder according to claim 1, characterized in that: The impurities are composed of antimony, arsenic and tin in a mass ratio of 2-5:1-3:5-9.

7. The corrosion-resistant iron-based alloy powder according to claim 6, characterized in that: The impurities are composed of antimony, arsenic and tin in a mass ratio of 4:2:

7.

8. The method for preparing the corrosion-resistant iron-based alloy powder according to any one of claims 1 to 7, characterized in that: Specifically, a formulated amount of chromium, nickel, molybdenum, titanium, carbon, rare earth elements, impurities and iron are placed in a vacuum induction furnace and heated until they are all melted into liquid. Then, they are atomized and dried through an atomizing nozzle under the conditions of nitrogen as an atomizing medium and water as a cooling medium for the outer periphery of the furnace body to obtain corrosion-resistant iron-based alloy powder.

Citation Information

Patent Citations

  • Sea water corrosion resistant low-alloy cast iron

    CN101225496A

  • Iron-based high-titanium wear-resistant surfacing flux-cored welding wire

    CN101664862A

  • Novel high-temperature wear-resisting iron-base alloy powder

    CN102672166A

  • High-compactness corrosion-resistant nickel-iron alloy

    CN105648340A

  • Diesel engine powder metallurgy valve seat

    CN109396443A